Pengembangan Komposit Berbahan Ebonit Dengan Kandungan Sulfur 30 PHR Yang Diperkuat Serat Rami Untuk Komponen Otomotif - Fawwaz, Fikria, Joko Sedyono, ST, M.Eng, Ph.D (2017)
Purpose of the research was to know tensile strength, izod impact and hardness of ebonit-based material with varied jute fiber weights of 0 Phr, 30 Phr and 50 Phr and to know results of composite surface by using SEM (Scanning Electron microscopy) photograph. Material of the composite was ebonit strengthened with jute fiber that had been immersed in 5% NaOH for 2 hours. Then, process of rubber mix started. Natural rubber mixed with chemical substances and jute fiber by using a two-roll mill machine and the rubber was vulcanized by using mold press machine at 150oC. Test of the composite used standard ASTMD D-638-02 for tensile strength, ASTM D-256-00 for izod impact test and SNI 0778:2009 for hardness test. Results of the testing obtained the highest tensile strength of 32.84 N/mm2 for ebonit composite strengthened with 30 Phr jute fiber. Highest yield strength of 73% was found in ebonit composite with jute fibers of 50 Phr. Hardness test and izod impact test found highest values of 97.70 shore scale for hardness and 31.33 j/mm2 for izod impact in the ebonite composite with fiber jute of 30 Phr. Based on observation of SEM photographs, it can be concluded that each ebonite composite strengthened with jute fiber indicated air bubbles on surface of the composite that had been caused by very poor interfacial adhesion between the fiber and matrix.